Penerapan Metode Apriori dalam Implementasi E-Commerce pada Toko Gorden - Taufiq Hidayah; Ahmad Zamsuri (IndoAI: Journal of Artificial Intelligence and Computational Logic, 2026)
Curtains are pieces of fabric or textiles used to block light and enhance the appearance of doors, windows, and the room as a whole as a decorative element of the home interior. The sale of curtains in Pekanbaru, especially at Toko Ola Gorden, still uses conventional methods that limit market reach and store development. This research aims to create an e-commerce system for Toko Ola Gorden and apply the Apriori Algorithm to determine product recommendations based on transaction data. The results of this study successfully designed and built an e-commerce system using the FAST method and applied the Apriori Algorithm to provide product recommendations based on sales transactions at Toko Ola Gorden. The results of product recommendations are obtained with a minimum support of 30% and confidence of 50%, where one of the results shows that the purchase of vitrase is followed by the purchase of curtains with a support value of 57.14% and confidence 80%.